Biokoagulan dari Daun Mangrove sebagai Koagulan Limbah Cair Industri Tahu - Aldriansah, Aldo; Acmad Abiyyu Yusuf Sinatrya Junardokham; Astuti, Dwi Hery; Wahyusi, Kidriari Nurma (Jurnal Fisika Unand, 2025)
The utilization of bio-coagulants derived from mangrove leaf tannins offers an eco-friendly alternative for treating tofu industry wastewater. This study aims to evaluate the effect of mangrove leaf weight and sonication time on extracted tannin content and its effectiveness in reducing pollution parameters. Extraction was conducted using a sonication–maceration method with 96% ethanol, varying leaf weights (10–50 grams) and sonication durations (20–100 minutes). Tannin content was analyzed by KMnO₄ titration, and the extract with the highest yield was applied to the coagulation process. The highest tannin yield (10.78%) was obtained using 50 grams of leaf and 100 minutes of sonication. Application of the bio-coagulant reduced BOD by 24.7%, COD by 29.1%, increased TSS by 49.3%, and raised the pH from 3.59 to 3.71. Although less efficient than alum, tannin shows potential as a natural coagulant. Further optimization involving coagulant combinations and pH adjustment is recommended to enhance performance.